Uma comparação entre o método dos elementos de contorno e o método das soluções fundamentais para problemas de Laplace - Falchetto, Vinicius Pires (2015)
In this work is compared the numerical performance of the Boundary Elements Method (BEM) and the classic Method of Fundamental Solutions (MFS) in solution of problems governed by Laplace’s Equation.They are similar methods, that use the idea of a fundamental solution, but shows some important distinctions. Its possible to make these different methods interact in the solution of some more complex problems, what implies in more knowledge of MFSparticularities, once the BEM is currently a method much more known, of notorious efficiency in diverse important applications. The MFShowever, faces a rediscovery from the intensification of the meshless discretization technics. This work compares the accuracy of both methods and examines some particularities of each method in simple, but important problems for the identification of the reach of each technic